Histoenzymic and biochemical alterations in rabid buffalo calves-An experimental study - SINGH, H; SINGH, C K (The Indian Journal of Animal Sciences, 2014)
Buffalo calves (9) were divided into 3 groups of 3 buffalo calves each to study the histoenzymic and biochemical altherations after experimentally infecting the buffalo calves with street rabies virus. In group 1, buffalo calves (2) were inoculated with 656865 MICLD50 of street rabies virus (SRV) via oral route. Normal mice brain (5ml) (NMB)suspension was inoculated via similar route to third buffalo calf serving as (3ml) was inoculated via similar route to third buffalo calf serving as control of the group. In group 3, buffalo calves (2) were inoculated with 394119 MICLD50 of SRV via inter-thecal route. NMB suspension (3ml) was inoculated via similar route to third buffalo calf serving as control of this group. In group 3, buffalo calves (2 were inoculated (0.5 ml) into each eye. The enzymic studies of succinic dehydrogenase, acetyle cholioneterase, adenosine triphosphatase, alkaline phosphatase and lactic dehydrogenase were conducted in cryostai sections of nervous tissues. The enzymic activity was affected y neutronal degeneration and necrosis tissues. The enzymic activity was affected by neuronal degeneration and necrosis during progression of experimental disease. Biochemical studies revealed that there was progressive decrease in the level of acetyl cholinesterase during the course of experimental rabies, however, there was no signififant change in the level of blood urea nitrogen and cholesterol.